2003
DOI: 10.1152/ajpregu.00668.2002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain glycogen after sleep deprivation vary with genotype

Abstract: Sleep has been functionally implicated in brain energy homeostasis in that it could serve to replenish brain energy stores that become depleted while awake. Sleep deprivation (SD) should therefore lower brain glycogen content. We tested this hypothesis by sleep depriving mice of three inbred strains, i.e., AKR/J (AK), DBA/2J (D2), and C57BL/6J (B6), that differ greatly in their sleep regulation. After a 6-h SD, these mice and their controls were killed by microwave irradiation, and glycogen and glucose were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 38 publications
3
37
0
1
Order By: Relevance
“…The no. of animals in each group for glycogen and glucose are, respectively, Con (14,14), Con SD (9, 10), Adxϩ (15, 16), and Adxϩ SD (8,8). *Significant differences between sleep-deprived animals and control groups (P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The no. of animals in each group for glycogen and glucose are, respectively, Con (14,14), Con SD (9, 10), Adxϩ (15, 16), and Adxϩ SD (8,8). *Significant differences between sleep-deprived animals and control groups (P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…While in one study, 12-h SD decreased glycogen in the cortex and in several other brain regions (hippocampus, striatum, midbrain, and thalamus) of adult rats (25), SD increased glycogen levels in the cortex of 59-day-old rats in another (16). Furthermore, 6-h SD had varied effects on brain glycogen levels in young rats (16) and adult inbred mouse strains (14). These studies found that 6-h SD increased glycogen in the cortex of C57BL/6J mice but not in 24-to 50-day-old rats or in AKR/J and DBA/2J mice.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…How the changes in brain and body metabolism that occur with changes in behavioral states relate to sleep function remains, however, unknown. So far, the evidence is based on glucose metabolism or gene expression related to metabolism of lipids and proteins (Kennedy et al, 1982;Everson et al, 1994;Cirelli and Tononi, 2000b;Netchiporouk et al, 2001;Franken et al, 2003;Brown, 2004;Mackiewicz et al, 2007;Vyazovskiy et al, 2008a). Changes in metabolism in living animals are regulated both locally (activitydependent) and globally through circulating humoral factors.…”
Section: Stimulation Of Cortical Cultures Induces Similar Changes In mentioning
confidence: 99%
“…Increased cerebral glycogen metabolism has also been observed in organisms exerting effort (Gruetter, 2003). However, this is "an unlikely end point of sleep's functional role in brain energy homeostasis" (Franken,Gip,8 preliminary draft (9/24/2006) Hagiwara, Ruby, & Heller, 2003). Glucose still must be metabolized to generate ATP for the hippocampus.…”
Section: Discussionmentioning
confidence: 99%